Teacher collectivity and career paths in the Chilean accountability context - Ortiz Mallegas, Sebastián Andrés (2023)
The educational policies of privatization and accountability have configured a context of increasing professional demands that have had an impact on the mechanisms of teacher professionalization and the development of their careers. Chile has been described in international literature as a case on the implementation of these regulations. Likewise, empirical evidence on teachers' professional trajectories has highlighted the role of the collective as a response to these policies, since the collective is a source of learning and identity for their professional development. This study analysed the place of the teaching collective in the professional trajectories of three teachers of Language and Communication in Chile. It analysed the notion of an "us and we" of reference in the context of the Chilean teaching career policy. Based on a qualitative paradigm with an internal narrative design, five to six interviews were conducted with each participating teacher. The narrative thematic content analysis showed a configuration of the collective within the framework of the reconstruction of individual trajectories, in duality and in response to an evaluation policy that devalues at this level. These results conclude a process of ambivalent identification with the teaching collective. The implications of the emergence of a collective discourse in the framework of individual trajectories are discussed.